2021 update on ATP-binding cassette (ABC) transporters: how they meet the needs of plants. Issue 4 (6th May 2021) - Do, Thanh Ha Thi; Martinoia, Enrico; Lee, Youngsook; Hwang, Jae-Ung
Abstract : Recent developments in the field of ABC proteins including newly identified functions and regulatory mechanisms expand the understanding of how they function in the development and physiology of plants.